Participants' Satisfaction With Family Involvement Meetings: Implications for Child Welfare Practice. (November 2018) - Ahn, Haksoon; Hartzel, Samantha; Shaw, Terry
Purpose: Bivariate and logistics regression analyses were conducted to examine the effectiveness of child welfare agencies' Family Group Decision-Making (FGDM) practices focused on strengthening families and positive outcomes for children. This study evaluates one mid-Atlantic state's implementation of a FGDM called family involvement meetings (FIMs) to improve family strengths and their active engagement in the service planning process. Methods: Through use of a FIM Feedback Survey, participants provided satisfaction feedback on the general FIM process and what factors are associated with their satisfaction and decision-making at the meeting. Results: Multiple factors of participant's engagement, incorporating family strengths, and the FIM facilitator's knowledge and skills had significant impacts on the participant's decision-making and overall FIM satisfaction score. Discussion: This study will contribute to examining FGDM facilitators' practices and effective outcomes of FIMs to improve the well-being, safety, and permanency outcomes for children and their families.